Pengaruh Penggunaan Media Canva Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran Geografi - Sucahyanto, Sucahyanto; A’Rachman, Fauzi Ramadhoan; Syifa, Isti (Jurnal Ilmiah Wahana Pendidikan, 2023)
Teaching and learning activities in the 21st century are demands for every educator and student. Education currently emphasizes the core foundations of literacy and numeracy skills, social and emotional skills, health, digital literacy, and data literacy. Media is needed that can accommodate the transfer of information and knowledge to students. This study aims to determine the effect of using Canva media on Geography subjects. Overall, the results of the study show that the use of Canva as a learning medium has an effect on student learning outcomes in Geography. The F count = 16.856 with a significance level of 0.000 <0.05. The magnitude of the correlation or relationship value in column R is 0.600. The coefficient of determination (R Square) is 0.360 which implies that the influence of the independent variable, namely the use of Canva media on the dependent variable, namely the learning outcome, is 36%.